Role of Teacher Self-Efficacy and Teacher Commitment in getting desired Students’ Learning Outcomes - Ashraf, Nahid; Jamal, Sajid (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
According to NCERT report on Learning Outcomes at Elementary Stage (2017), learning outcomes refer to the assessment standards indicating the expected levels of learning that children should achieve for that class. There are many internal and external factors that affect students learning outcome at different stages. Among all the factors, teachers are one of the most important factors that affect students learning outcomes and play crucial role in their overall personality development. Therefore, it is essential to ensure the quality of teachers for getting quality education and desired learning outcomes. Teacher self-efficacy is one of the important factors affecting Learning outcome is considered as the belief of teacher in his/or her own teaching ability to do the teaching task successfully and affect the student‘s achievement. It also determines the performance of the teachers as well as their success and failure in teaching task. Since, commitment of teachers is considered as the important attribute for ensuring the quality of teachers as well as the whole education system as it ensures the retention of the teachers in the profession as well as in the organization, hence, it should have positive correlation with the teacher self-efficacy. But very few studies have been conducted in this regard. Therefore, this study was conducted to examine the impact of various components of organizational commitment on teacher self-efficacy. For this, a self-constructed Teacher Self Efficacy Scale and a standardised Organizational Commitment Scale were administered on 400 secondary school teachers of Aligarh District of U.P. Analysis of the data was done by calculating coefficient of correlation and step-wise multiple regression analysis and it has very relevant findings for teachers and policy makers.